An analysis and design for time-varying structures dynamical networks via state constraint impulsive control. Issue 12 (2nd December 2019) - Li, Liangliang; Li, Chuandong; Li, Hongfei
ABSTRACT: This paper investigates the problems of exponential stabilisation criterion for time-varying structures dynamical networks via state constraint impulsive control. Two types of state constraint impulsive control schemes are proposed which include fully state constraint and partial state constraint. Combining with convex analysis, inductive method and matrix measure theory, some sufficient conditions are obtained to ensure exponential stabilisation for time-varying structures dynamical systems by using the constrains linear feedback impulsive controllers. Meanwhile, some simulation results are given to validate the effectiveness of the proposed criteria in the end.